2018
DOI: 10.1111/jfs.12598
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of bacterial human pathogens on tomato skin surfaces using eugenol‐loaded surfactant micelles during refrigerated and abuse storage

Abstract: The plant‐derived essential oil component eugenol (1.0% wt/vol), free or loaded into surfactant micelles constructed of sodium dodecyl sulfate (SDS; 1.0% wt/vol), 200 ppm free chlorine (hypochlorous acid [HOCl]; pH 7.0), and sterile distilled water were evaluated for their ability to reduce Salmonella Saintpaul and Escherichia coli O157:H7 on skin surface samples of Roma tomatoes. Samples were treated and then stored aerobically for up to 10 days. All samples were initially stored at 5 °C; one set of samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Plant-derived antimicrobials (PDAs) make attractive produce disinfectants due to their natural origin, compatibility with various produce commodities, and utility against microbial pathogens (Yoon and Lee, 2018). Nonetheless, PDA utility is often limited due to inherent volatility and, in some instances, low water solubility (Ruengvisesh et al, 2019b). One strategy to overcome these limitations of PDAs is to encapsulate them in a water-miscible system to facilitate their delivery to produce surfaces, potentially improving on observed antimicrobial effects (Yegin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Plant-derived antimicrobials (PDAs) make attractive produce disinfectants due to their natural origin, compatibility with various produce commodities, and utility against microbial pathogens (Yoon and Lee, 2018). Nonetheless, PDA utility is often limited due to inherent volatility and, in some instances, low water solubility (Ruengvisesh et al, 2019b). One strategy to overcome these limitations of PDAs is to encapsulate them in a water-miscible system to facilitate their delivery to produce surfaces, potentially improving on observed antimicrobial effects (Yegin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al [22] showed that cinnamon leaf essential oil in cetylpyridinium chloride produced 1.8 and 1.5 log 10 CFU/g reductions against L. monocytogenes and E. coli O157:H7, respectively; quality of kale leaves was not affected during storage. In our previous study, eugenol (1% w/v ) encapsulated in SDS (1% w/v ) micelles were used for inhibition of S. Saintpaul and E. coli O157:H7 as well as native microbiota on tomato skin surfaces during refrigerated and abuse storage [28]. In that study, antimicrobial effects of free and encapsulated eugenol did not differ from those of HOCl and empty SDS micelles during refrigerated storage.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, antimicrobial effects of free and encapsulated eugenol did not differ from those of HOCl and empty SDS micelles during refrigerated storage. However, reductions in pathogen counts to non-detectable levels were only observed with free and encapsulated eugenol [28]. EOC-encapsulated micelles could be used as an alternative to the commonly used sanitizers to reduce pathogens on fresh produce, potentially achieving greater pathogen reductions versus those typically observed by washing in chlorinated water [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To provide a framework for the deductive selection of an effective sample preparation technique, particle size, composition and bacterial retention both pre-and post-implementation were analyzed for several sample preparation methods including continuous flow centrifugation, glass wool, graphite felt, and 50 µm polypropylene filters. Although there is concern regarding the ability of bacteria to bind to matrix components [40][41][42][43], the study herein did not attempt to incorporate a "release agent" [44][45][46][47][48] and simply added the inoculum to the matrix without an incubation step to lessen the likelihood of bacteria/ matrix interactions and avoid confounding the analysis. However, we acknowledge this concern and recognize that addition of any such agent may alter the effects of the clarification processes presented here.…”
Section: Discussionmentioning
confidence: 99%